ANALISIS PENGARUH BIAYA AUDIT RELATIF TERHADAP LOYALITAS KLIEN PADA PASAR AUDIT DI INDONESIA - Karina Febri Ramadhani; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
This study aims to examine impact of audit fees relative to client loyalty and degree of loyalty . The independent variables of this study are relative audit fees and the dependent variable is loyalty and degree of loyalty by being influenced by other factors namely Big 4, Company Size, Company Growth, and Leverage. The research data is secondary data from financial statements and annual reports from companies of all sectors listed on the Indonesia Stock Exchange in 2011-2017. The research sample was obtained using a sample collection method, namely purposive sampling. The total sample of this study was 152 companies. This study uses the method of logistic regression analysis and ordinal logistic analysis. The findings of this study indicate that there is a negative influence on audit costs relative to client loyalty and the level of client loyalty.